1977
DOI: 10.1002/mpo.2950030114
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity Due to CNS Therapy for Leukemia

Abstract: CNS symptoms ranging from mild to lethal have occurred following CNS radiotherapy and intrathecal chemotherapy. Cranial radiotherapy often produces signs of mild encephalopathy, with predominance of somnolence. In rare cases, it appears that CNS radiotherapy may be followed by progressive encephalopathy. Intrathecal methotrexate frequently causes symptoms of meningeal irritation. Occasionally cases of weakness and paralysis, and rare instances of severe encephalopathy, may occur. However, in leukemic children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1978
1978
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 45 publications
(69 reference statements)
0
15
0
1
Order By: Relevance
“…1 On the basis of the impressive results obtained in the pilot trial of the Memorial Sloan-Kettering Cancer Center, 2 92% complete remission (CR) rate in relapsed APL patients, in the United States a multicenter study has been conducted to evaluate the efficacy and tolerability of As 2 O 3 for remission induction and consolidation in a larger population of APL patients who had relapsed from prior retinoic and anthracycline-based chemotherapy. 3 In this study the authors reported an 85% CR rate with a relapse free survival rate at 18 months of 56%.…”
Section: To the Editormentioning
confidence: 63%
See 2 more Smart Citations
“…1 On the basis of the impressive results obtained in the pilot trial of the Memorial Sloan-Kettering Cancer Center, 2 92% complete remission (CR) rate in relapsed APL patients, in the United States a multicenter study has been conducted to evaluate the efficacy and tolerability of As 2 O 3 for remission induction and consolidation in a larger population of APL patients who had relapsed from prior retinoic and anthracycline-based chemotherapy. 3 In this study the authors reported an 85% CR rate with a relapse free survival rate at 18 months of 56%.…”
Section: To the Editormentioning
confidence: 63%
“…Leukemia neurotoxicity. [2][3] The CSF clearance of ara-C is similar to that of the CSF bulk flow rate. Furthermore, there is little conversion of ara-C to uracile arabinoside in the brain and CSF.…”
Section: To the Editormentioning
confidence: 92%
See 1 more Smart Citation
“…It is known that patients who tend to develop MTX leukoencephalopathy are those who had active CNS involvement at the initiation of therapy [2,10,11]. Diagnostic tests to screen for subclinical progressive neurotoxicity would be valuable adjuncts in planning or altering CNS therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Three major syndromes have been described: meningeal irritatiodarachnoiditis , paraplegia, and encephalopathy [2,11]. The leukoencephalopathy syndrome is manifested by chronic progressive confusion, poor school performance, somnolence, tremor, ataxia, and dementia.…”
Section: Introductionmentioning
confidence: 99%